Semiotic Analysis of Emotional Meaning in the Lyrics of "See You Again" by Charlie Puth, Wiz Khalifa, Justin Franks, and Andrew Cedar - Ni Komang Sri Wardani; Ni Putu Artila Dewi; Ni Made Ayu Purnami (Jurnal Media Informatika, 2026)
Music is an artistic form that can transmit feelings and societal messages. Banoe (2003) argues that music arranges sounds in comprehensible patterns. The art of arranging tones to create a harmonic composition is what the Big Indonesian Dictionary defines as music. The song "See You Again" by Wiz Khalifa and Charlie Puth, released in 2015, is an illustration of how music blends social messages with feelings. The song, which was written as a memorial to Paul Walker, explores themes of friendship, hope, and sadness. The song reached the top of the Billboard Hot 100 and became a worldwide sensation after receiving over 6.3 billion views on YouTube. Using critical discourse analysis and Ferdinand de Saussure’s semiotic theory, this study examines the lyrics of "See You Again" in order to determine the emotional meaning they convey. Exhaustion, an emotional voyage, and hope for a reunion are all described in the lyrics, according to the signifier and sign analysis. This study demonstrates how the song's lyrics inspire a universal message about friendship and loss while also establishing a strong emotional bond with the listener. Key word : music, semiotics, emotional meaning, song lyrics, see you again.